2021
DOI: 10.3390/tomography7040063
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Remineralization Competence of a Novel Fluoride-Incorporated Bioactive Glass Toothpaste—A Surface Micro-Hardness, Profilometric, and Micro-Computed Tomographic Analysis

Abstract: This study aimed to analyze the enamel remineralization efficacy of a novel fluoridated bioactive glass (F-BG) toothpaste compared to a standard fluoride toothpaste. Seventy-two enamel blocks (N = 72) were divided into groups of twenty-four blocks according to the toothpaste exposure—group 1: brushed with distilled water, group 2: brushed with fluoride toothpaste (ColgateTM), and group 3: brushed with F-BG toothpaste (BioMinFTM). Pre-brushing, enamel blocks were demineralized using 6 wt.% citric acid (pH = 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Based on the Mann-Whitney test, there was a significant difference between each group that was soaked in saliva, the group that was demineralized, the group that was applied CPP-ACP and the group that was given 15% goldfish scale hydroxyapatite paste, which was evidenced by a significance value of p = 0.000 (p<0.05). The variation in surface hardness values in the average sample is thought to be related to the patient's genetics, which affects the thickness of the enamel layer, surface hardness, the age of the patient's teeth, and the duration from extraction to treatment [17]. The thicker the tooth enamel, the higher the surface hardness value.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Mann-Whitney test, there was a significant difference between each group that was soaked in saliva, the group that was demineralized, the group that was applied CPP-ACP and the group that was given 15% goldfish scale hydroxyapatite paste, which was evidenced by a significance value of p = 0.000 (p<0.05). The variation in surface hardness values in the average sample is thought to be related to the patient's genetics, which affects the thickness of the enamel layer, surface hardness, the age of the patient's teeth, and the duration from extraction to treatment [17]. The thicker the tooth enamel, the higher the surface hardness value.…”
Section: Resultsmentioning
confidence: 99%
“…Fluoride and CPP-ACP + fluoride exhibited similar results, and CPP-ACP increased the enamel mineral density and decreased the depths of lesions. Farooq et al [42] brushed teeth with fluoride, bioactive glass, and distilled water in their in-vitro study, and revealed that the enamel volume decreased after demineralization and increased after remineralization in all groups according to micro-CT analysis. Similarly, in our study, Sensodyne Promine provided the greatest volume increase.…”
Section: Discussionmentioning
confidence: 99%
“…Microhardness was measured using the Vickers hardness number on the buccal surface of all specimens at five random spots using a hardness testing machine (MVK-H1 Akashi, Kanagawa, Japan). [33][34][35] Each specimen was subjected to five indentations and the average hardness value was calculated. The applied load was 100 gf, with a dwell time of 10s.…”
Section: Microhardness Testmentioning
confidence: 99%